Застосування методології консолідованого маркетингу для вирішення проблем збуту підприємств галузі сільськогосподарського машинобудування - Нехай, Вікторія Василівна; Нехай, Виктория Васильевна; Nekhai, Viktoriia (My University, 2018)
UK: Означені протиріччя у співвідношенні таких проблем, як низький рівень збуту сільгосптехніки та слабка забезпеченість сільського господарства країни технікою. Вказано на існуючі методи вирішення проблем збуту сільськогосподарської техніки та обгрунтовано доцільність опрацювання нових методів та підходів. Наведено роз’яснення поняття «консолідація» у застосуванні до маркетингу у діяльності підприємств галузі сільськогосподарського машинобудування України. Визначено пріоритети розвитку галузі. Наведені думки вітчизняних та закордонних авторів щодо ділового партнерства у збуті продукції. EN: The purpose of this article is to present conditions and general directions of study and methods transformation of marketing in consolidated form of marketing. To achieve the goal used methods: empirical, analysis, synthesis, comparison. In the industry of agricultural machinery Ukraine are defining problems. The consequence of these problems is the poor performance of sales. Our agriculture provided enough equipment. At one company accounts for agriculture combine 0.6 and 2.7 of the tractor. These problems successfully solved with the help of an individual election and forms of marketing. Marketing aims to develop specialized markets to promote innovation, updating the range. Nowadays enterprises solve marketing problems through intermediaries. Intermediaries concentrated its efforts on the material - technical support of agriculture, maintenance and service offering of stock trading. Specified that the intermediaries is both the subsidiary and complicating factor. The purpose of the consolidated marketing for agricultural machinery is to improve sales. This led to the novelty of the study. Clarification of the concept of "consolidation of marketing" helps to understand its feasibility to improve marketynhovooho impact on improving sales. When applied to the research topic is meant by consolidation and compaction marketing associations marketing efforts for solving the problems of sales of agricultural engineering enterprises. This is consistent with the basic principles of economic development of Ukraine as industrially - agrarian country There is a need to study foreign experience in solving the problems of sales. In view of the marketing problems should take into account experience and form output to overseas markets. Thus, had the further development of the conceptual basis of the opportunities by consolidating marketing efforts to sales of agricultural machinery. Developed of Categories - conceptual apparatus "consolidation of marketing" toward a specific interpretation of the term. Require further study and practical application of new approaches to developing drugs sales organization based on consolidated marketing that can be effective both in domestic and foreign markets.
Application of consolidated marketing methodology for solving problems of agricultural machine building enterprises
Keywords: збут; консолідація; маркетинг; ринок; сільськогосподарське машинобудування; технічне забезпечення; consolidation; market; marketing; realization; agricultural engineering; technical support